KEKUATAN PEMBUKTIAN SURAT PEMESANAN (PURCHASE ORDER) YANG TERLAMBAT TERBIT - Danny Maulana Sofian Aziz; Endang Prasetyawati (Gapenas Publisher, 2023)
Purchase Order system is a common practice in the buying and selling business, the buyer issues a Purchase Order and the seller sends the products according to the Purchase Order. In the business of buying and selling healthcare equipment, there is a special condition in which the seller sends the products before the Purchase Order is issued. The purpose of this study was to determine the proven power of the late Purchase Order as a purchase agreement in the field of healthcare. This study used a juridical normative research method with a legislative and case approach. The conclusion of this study is that the late Purchase Order as a letter of order is a valid promissory document and can be used as a proof if there is a problem with the transaction